The plasma lipopolysaccharide level is associated with contrast-induced acute kidney injury in patients with ST-segment elevation myocardial infarction - Haiqiang Shen; Qinghuan Yang; Xiaofu Zhang; Shan Qin; Yong Li; Jinqi Liu (BMC Cardiovascular Disorders)
Abstract Background Lipopolysaccharide (LPS) plays an important role in cardiovascular and renal diseases. However, the relationship between LPS and contrast-induced acute kidney injury (CI-AKI) remains unclear. This study aimed to investigate the role of LPS in patients with ST-segment elevation myocardial infarction (STEMI) and its relationship with CI-AKI following percutaneous coronary intervention (PCI). Methods This single-centre retrospective observational study included 710 patients diagnosed with STEMI. CI-AKI was defined as an increase in SCr of at least 50% or 0.3 mg/dL within 48–72 h after contrast exposure. Regression analysis was used to identify potential risk factors. Restricted cubic splines (RCSs) were used to explore the dose‒response relationship between LPS levels and CI-AKI. The models were evaluated using receiver operating characteristic (ROC) curves, the net reclassification index (NRI), and the integrated discrimination improvement (IDI) index. Results The incidence of CI-AKI during hospitalization was 12.5%. After adjusting for potential confounding factors, the results revealed that LPS (OR = 0.650, 95% CI: 0.466–0.906) was an independent risk factor that affected the occurrence of CI-AKI. The RCS results revealed a linear dose‒response relationship between LPS and CI-AKI. After integration of LPS, the model demonstrated a significantly improved ability to predict CI-AKI (IDI 0.095, P < 0.001; NRI 0.720, P < 0.001). Conclusion Elevated LPS is an independent risk factor for the development of CI-AKI after PCI in patients with STEMI. The integration of LPS detection significantly improved the risk model for CI-AKI.